2022
DOI: 10.3390/ijerph192113858
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from an Attempted Pragmatic Randomized Controlled Trial for Improvement of Chronic Pain-Associated Disability in Green Professions: Long-Term Effectiveness of a Guided Online-Based Acceptance and Commitment Therapy  (PACT-A)

Abstract: Musculoskeletal symptoms are increased in farmers, whereas the prevalence of chronified pain is unknown. Online interventions based on acceptance and commitment therapy (ACT) have shown encouraging results in the general population, representing a promising approach for reducing pain interference in green professions (i.e., farmers, foresters, gardeners). We conducted a pragmatic RCT comparing a guided ACT-based online intervention to enhanced treatment-as-usual in entrepreneurs, contributing spouses, family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…However, the current power of the study as well as the unequal number in the groups did not allow for a significance test. As the results of the accompanying randomized controlled trials show ( 28 30 , 34 ), both interventions effectively reduce depressive symptoms posttreatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the current power of the study as well as the unequal number in the groups did not allow for a significance test. As the results of the accompanying randomized controlled trials show ( 28 30 , 34 ), both interventions effectively reduce depressive symptoms posttreatment.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, “time-consuming work life” and “time-consuming private life” were the most often mentioned barriers regarding intervention use ( 32 ). However, besides RCT participation, in which low adherence regarding intervention use ( 28 , 29 ) and recruitment difficulties ( 34 ) are reported for IBIs, not much is known about routine care use. Therefore, it is critical to understand the factors that influence the uptake and implementation of both digital health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies reported ACT training specifically for the trial [46,56]. Thirteen studies documented whether client engagement checks were conducted during the trial [28,29,46,47,49,50,52,53,[56][57][58][59][60].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Moreover, by combining Mindfulness-Based Stress Reduction and ACT in the tailored intervention, the research not only enhanced the intervention's relevance and effectiveness but also offered valuable methodological insights for future ACT research in chronic pain management [28]. Lina's 2022 research used an automated web program for individual-level crossover block randomization to ensure fair allocation across study arms [29]. A blinded third party unconnected to the research conducted the randomization and allocation, while data collectors were kept unaware of participant groups [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation